Impact of vocational rehabilitation on social functioning, cognitive functioning, and psychopathology in patients with chronic schizophrenia - Suresh Kumar, P. N. (Medknow Publications, 2008)
AIM: To assess the impact of vocational rehabilitation on psychopathology, social functioning and cognitive functioning in schizophrenia MATERIALS AND METHODS: 34 patients with DSM IV diagnosis of chronic schizophrenia were compared 40 patients with same diagnosis but not attending vocational rehabilitation using PANSS, SCARF social functioning Index and MMSE. RESULTS AND DISCUSSION: Basic psycho-socio-demographic data were comparable in both groups except more hospitalization in the no rehabilitation group. Comparison of social functioning, cognitive functioning and psychopathology showed significant improvement in rehabilitated patients. Cognitive functioning had positive correlation with occupational role in the rehabilitated group and negative correlation in the rehabilitated group. Social functioning had negative correlation with positive and negative symptoms, general psychopathology and total PANSS score and cognitive symptoms in patients without rehabilitation. CONCLUSION: The present concludes that there is a definite limitation in the domains of social functioning, cognitive functioning and psychopathology in chronic schizophrenia patients who had no rehabilitation. However vocational rehabilitation significantly improves these limitations, which in turn help these patients to integrate into the society so as to function efficiently in their roles as parents, home makers and social beings.